CO2 Permeation Behavior through Carbon Membranes: A Short Review of the Progress during the Last Decade - Favvas, Evangelos P. (Journal of Membrane and Separation Technology, 2016)
Although carbon dioxide is not classified as a toxic or harmful gas the necessity for its capture is enforced not only by scientists but also by governments worldwide. In this attempt the technologies which are proposed to attend this role are various. Contrary to the traditional thermal methods (distillation, adsorption, cryogenic), which require high energy sources, the membrane technology seems to be the prevalent solution mainly thanks to its low operation cost. To this aim, both polymeric and inorganic membranes are reported as good candidates for CO2 separation–capture. The main advantages of the inorganic membranes, in terms of the polymeric, are their higher selectivity factors and the better stability at both high temperatures and chemical environments. The preparation of the carbon membranes takes place mainly by the controlled pyrolysis of different thermosetting polymeric materials and the final configuration can be divided into the following configurations: i) flat sheet membranes, ii) supported on tube membranes, iii) capillary membranes and iv) hollow fiber membranes. During the last fifty years, more attention has been devoted, not only for the simultaneous increase of both permeability and selectivity factors but also for the large–scale production of crack free carbon membranes. The reproductivity is also one critical point which has to be achieved if we really aim for the industrial application of the carbon gas selective membranes. Therefore, carbon membranes have the potential to be the materials of the future for many gas separation processes including the one of carbon dioxide separation–capture. This paper is reviewing the development and the achievements of the carbon membranes in the direction of the CO2 separation giving emphasis on the last 10 years.